The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1108/jocm-05-2016-0106
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between universal network perceptions and dyadic network perceptions and their effect on employees’ behavioral reactions to organizational change

Abstract: Purpose The purpose of this paper is to examine empirically the relationships formed between the universal network quality perceptions and the dyadic network quality perceptions that an individual formulate through social ties at work and their effect on behavioral reaction toward organizational change. Design/methodology/approach The data were collected from 91 full-time hotel employees through a self-report survey. Using regression models and mediation method three hypotheses referring to the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 64 publications
3
8
0
Order By: Relevance
“…Therefore the authors decided to use the five dimensional TERRA model (Zeithaml et al , 1990) to test employee’s ability to recall the overall structure of their connections because can be coded and retrieved much easier and faster by the brain (Brashears and Quintane, 2015). This evidence is compatible with previous researchers’ findings where relationship quality is approached as a multidimensional construct (Granovetter, 1973; Hatjidis and Parker, 2017; Marsden and Campbell, 1984;) that has a positive effect on the behavioral patterns toward change (Hatjidis and Parker, 2017; Marsden and Campbell, 1984), and thus can become a conduit of positive psychological influence. İn addition, this particular finding adds to the current scholarship that seeks to clarify and understand the various ways positivity can have an impact on organizational change (Avey et al , 2008) compared to negative influences that cause employees’ resistance to change.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore the authors decided to use the five dimensional TERRA model (Zeithaml et al , 1990) to test employee’s ability to recall the overall structure of their connections because can be coded and retrieved much easier and faster by the brain (Brashears and Quintane, 2015). This evidence is compatible with previous researchers’ findings where relationship quality is approached as a multidimensional construct (Granovetter, 1973; Hatjidis and Parker, 2017; Marsden and Campbell, 1984;) that has a positive effect on the behavioral patterns toward change (Hatjidis and Parker, 2017; Marsden and Campbell, 1984), and thus can become a conduit of positive psychological influence. İn addition, this particular finding adds to the current scholarship that seeks to clarify and understand the various ways positivity can have an impact on organizational change (Avey et al , 2008) compared to negative influences that cause employees’ resistance to change.…”
Section: Discussionsupporting
confidence: 93%
“…In relation to that, prior empirical findings have explained relationship quality as a multidimensional construct that is composed of emotional (Granovetter, 1973), psychological (Ragins et al , 2000) and technical (Marsden and Campbell, 1984) characteristics. In addition, it has been found that the universal network perception of an individual’s relationship quality can have a significant positive effect on their behavioral patterns toward change (Hatjidis and Parker, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, by recognising the impact of his/her networking behaviours, network characteristics and leaders’ network position on followers' shared image of the leader, a leader will be in a better position to more effectively manage his/her networks and behaviour to increase his/her influence. This is consistent with the idea that overall network perception is more important to behavioural intention than dyadic perceptions (Hatjidis and Parker, 2017) which have been the focus of LMX theory in the past.…”
Section: Discussionsupporting
confidence: 89%
“…Previous research indicates that follower social networks can influence the emergence and effectiveness of leadership (Avolio et al , 2009). Additionally, universal network perception has been positively associated with behavioural intention, contrary to dyadic perceptions (Hatjidis and Parker, 2017). By focussing on the whole network dynamics, we can have a better understanding of leader/follower behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is interesting that research is increasingly studying willingness to change and the associated emotional processes (cf. Hatjidis and Parker, 2017). However, to our knowledge, few studies of individual dispositions have sought to examine how change and adaptation can be embraced as an emotional process.…”
Section: State Of the Art And Future Research Agendamentioning
confidence: 99%